DIVERSITY OF PLANTS USED BY THE URARINA PEOPLE IN THE LORETO DEPARTMENT, PERU - ZÁRATE-GÓMEZ, Ricardo (2024)
The numerous scientific publications related to the use of plants by the Urarina people demonstrate a deep-seated and valuable knowledge. However, it lacks a comprehensive review that encompasses this vast botanical knowledge. In this regard, our goal was to understand the diversity of plants used by the Urarinas in the Loreto region (Peru). To achieve this, we conducted a thorough literature review of scientific publications, where we found 17 publications with data on plant use related to the Urarina people. We recorded 196 species of flowering plants included in 56 families. The palm family (Arecaceae) stands out as the family with the greatest variety of uses, with its ten representative species: Iriartea deltoidea, Bactris gasipaes, Mauritia flexuosa, Oenocarpus bataua, Euterpe precatoria, Socratea exorrhiza, Oenocarpus mapora, Attalea phalerata, Elaeis oleifera and Phytelephas tenuicaulis. This finding highlights the cultural importance of palms in traditional Urarina practices; moreover, it provides a solid foundation for future ethnobotanical research and conservation strategies